(untitled) (Research, Society and Development, 2022)
This work starts from the locus of scientific initiation in Vocational and Technological Education (EPT), developed at the Federal Institute of Paraíba, Campus Pedras de Fogo. Its objective is to point out some of the perspectives of the practice of scientific initiation at EPT, having the field of gastronomy as a reference. It is from the perspective of multi-interdisciplinary, from the contribution of the areas of knowledge of informatics, nutrition and psychology, that the project “Construction of an application with techniques and recipes for the development of gluten-free and casein-free foods for children autistics” achieves its preliminary goals. In this sense, this study starts from research with a qualitative approach, exploratory objective and action-research type procedure. This research shows, based on the engagement of the participating students, in the demands of contemporary society, the importance of the research and teaching relationship. Furthermore, the formative perspectives noted here are in accordance with the EPT guidelines.